Corelation Between Emotional Intelligenceand Self-Efficacy With Mastery of Kayak Roll Slalom Technique - Ramdhani Rahman; Nurlan Kusmaedi; Komarudin Komarudin (STKIP Muhammadiyah Kuningan, 2019)
The aim of this research is to know the relationship between emotional intelligence, self efficacy and emotional intelligence with self efficacy simultaneously towards the technique mastering of roll kayak slalom The research method used is quantitative descriptive method. The research design used in this study was a correlation design with a population of 40 canoeing athletes who were conducting regional training to deal with PON XX Papua, the sampling technique used purposive sampling with the criterion of athletes in training the slalom race number with a sample of 12 athletes , which consists of 6 men and 6 women. The instruments used were emotional intelligence questionnaires, self-efficacy models and eskimoroll technique instruments. The results showed that there was a relationship seen simultaneously there was a strong relationship between emotional intelligence and self efficacy with mastery of techniques roll like slalom. The conclusion of this study states that there is a relationship between emotional intelligence and mastery of roll techniques such as slalom, there is a relationship between self-efficacy with mastery of roll techniques like slalom, simultaneously there is a relationship between emotional intelligence and self-efficacy with mastery of roll technique like slalom.